PROJECT-BASED LEARNING: OPTIMIZING STUDENTS’ CRITICAL THINKING SKILLS - Mimin Aminah (LPSDI Bina Patria, 2024)
Project-based learning is basically a learning activity that provides space for students to fully learn the scientific competencies need to be mastered. Moreover, this activity also provides space for students to optimize their critical analysis skills towards an issue. The project encourages students to look for creative alternative solutions to solve problems and provide responses to these phenomena. This research conducted descriptive qualitative research design with 3 purposive sampling text. This research show that project-based learning effective to optimizing students’ critical thingking with the following indicators: problem identification, clarifying question, logic of argument, evidence/supportive information, synthesis of ideas, references to readings, and problem solving. Furthermore, Critical Thingking skill is basic to help the students look an issue with a good point of of view by finding a logic of argument tha relate with the issue.